Islamic Music Therapy Through Sholawat Jibril Audio to Grow Self Acceptance in the Elderly - Kumaini, M. Hafid; Yasinta, Nindya Pujiati (Da’wa and Communication Faculty of the Sunan Ampel State Islamic University, Surabaya, Indonesia., 2021)
Lack of self-acceptance often occurs in someone who is old or elderly who has been abandoned by his wife or husband and left by their children who have built their own household. Islamic Music Therapy through audio Sholawat Jibril is a therapy that aims to calm the heart and always invites to increase spirituality by remembering Allah and Rasulullah SAW. This study uses a qualitative approach, namely the research phase that produces descriptive data in the form of written or spoken words instead of numbers (non-statistical) from the people and observed behavior. Qualitative research is obtained from interviews, observations, documentation. Therefore, Islamic music therapy through audio Sholawat Jibril in the program for growing self-acceptance in the elderly is able to grow self-acceptance and positive things that will be very necessary for an effort to increase spiritual feelings in the elderly. With this prayer, it is possible for the elderly to be able to develop reduced self-acceptance due to the condition that they are old and their relatives who have left the elderly alone.